2020
DOI: 10.1002/trtr.1950
|View full text |Cite
|
Sign up to set email alerts
|

Metatalk Moves: Examining Tools for Collective Academic Discourse Learning

Abstract: To leverage what students know about language in the service of creating a rich classroom language environment, teachers must recognize and build on students' metatalk moves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Across these succesful interventions,academic language was not considered a prerequisite for participation or taught in isolation from the content and concepts it evolved to express. In other words, academic language is most effectively taught to middle grade readers by providing explicit instruction in new language forms and by offering students opportunities to participate in authentic tasks that call for using academic language: extended discussions of big ideas and conceptual knowledge contained in texts, opportunities to engage with print that contains academic language, multiple chances to use this language when writing for authentic audiences, and opportunities to reflect on language‐in‐use using metatalk (Jones et al, 2019; Lawrence, Crosson, Paré‐Blagoev, & Snow, 2015; Phillips Galloway & McClain, in press; Proctor et al, 2020; Wasik & Hindman, 2018). This context‐embedded, authentic instruction is further supported by a conceptualization of academic language that extends beyond cognitive skill to consider sociocultural functions within academic discourse communities.…”
Section: Readers’ Academic Language Skills and Social Practices: Three Key Understandingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across these succesful interventions,academic language was not considered a prerequisite for participation or taught in isolation from the content and concepts it evolved to express. In other words, academic language is most effectively taught to middle grade readers by providing explicit instruction in new language forms and by offering students opportunities to participate in authentic tasks that call for using academic language: extended discussions of big ideas and conceptual knowledge contained in texts, opportunities to engage with print that contains academic language, multiple chances to use this language when writing for authentic audiences, and opportunities to reflect on language‐in‐use using metatalk (Jones et al, 2019; Lawrence, Crosson, Paré‐Blagoev, & Snow, 2015; Phillips Galloway & McClain, in press; Proctor et al, 2020; Wasik & Hindman, 2018). This context‐embedded, authentic instruction is further supported by a conceptualization of academic language that extends beyond cognitive skill to consider sociocultural functions within academic discourse communities.…”
Section: Readers’ Academic Language Skills and Social Practices: Three Key Understandingsmentioning
confidence: 99%
“…Observation measures could, for example, contain indicators that examine whether teachers support learner agency in text interpretation, recognize students’ skillful use of home language as comprehension resources, and foster critical refection on dominant interpretations of the academic language of print. Our experiences in classrooms that promote this type of text analysis have suggested that much of this work is done collectively (Phillips Galloway & McClain, in press). For this reason, studies of classroom discourse, in particular, offer a useful analytic tool kit that could be productively applied to make more visible these aspects of classroom pedagogy that position readers as more or less agentive (see, e.g., Godley & Reaser, 2018; O’Connor & Michaels, 2015; O’Connor, Michaels, Chapin, & Harbaugh, 2017); however, these studies have mostly focused on microanalysis of classroom episodes (using frameworks such as critical discourse analysis, interactional sociolinguistics, or conversation analysis) and not generally been directed toward creating classroom observational measures that could be used more widely to inform the science of reading.…”
Section: (Re)conceptualizing Academic Language Comprehension: Implications For the Science Of Readingmentioning
confidence: 99%